PISA: Efficient Precision-Slice Framework for LLMs with Adaptive Numerical Type - Yang, Ning; Wang, Zongwu; Sun, Qingxiao; Lu, Liqiang; Liu, Fangxin (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Large language models (LLMs) have transformed numerous AI applications, with on-device deployment becoming increasingly important for reducing cloud computing costs and protecting user privacy. However, the astronomical model size and limited hardware resources pose significant deployment challenges. Model quantization is a promising approach to mitigate this gap, but the presence of outliers in LLMs reduces its effectiveness. Previous efforts addressed this issue by employing compression-based encoding for mixed-precision quantization. These approaches struggle to balance model accuracy with hardware efficiency due to their value-wise outlier granularity and complex encoding/decoding hardware logic. To address this, we propose PISA (Precision-Slice Framework), an acceleration framework that exploits massive sparsity in the higher-order part of LLMs by splitting 16-bit values into a 4-bit/12-bit format. Crucially, PISA introduces an early bird mechanism that leverages the high-order 4-bit computation to predict the importance of the full calculation result. This mechanism enables efficient computational skips by continuing execution only for important computations and using preset values for less significant ones. This scheme can be efficiently integrated with existing hardware accelerators like systolic arrays without complex encoding/decoding. As a result, PISA outperforms state-of-the-art precision-aware accelerators, achieving a 1.3-4.3 × performance boost and 14.3-66.7 % greater energy efficiency, with minimal model accuracy loss. This approach enables more efficient ondevice LLM deployment, effectively balancing computational efficiency and model accuracy.